2012
DOI: 10.1152/jn.00256.2011
|View full text |Cite
|
Sign up to set email alerts
|

Foot anatomy specialization for postural sensation and control

Abstract: Wright WG, Ivanenko YP, Gurfinkel VS. Foot anatomy specialization for postural sensation and control. J Neurophysiol 107: 1513-1521, 2012. First published December 7, 2011 doi:10.1152/jn.00256.2011.-Anthropological and biomechanical research suggests that the human foot evolved a unique design for propulsion and support. In theory, the arch and toes must play an important role, however, many postural studies tend to focus on the simple hinge action of the ankle joint. To investigate further the role of foot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 53 publications
1
79
0
3
Order By: Relevance
“…Then, we need to adapt our locomotor pattern to compensate for the dysfunction. The research revealed that even a partial loss of the toes not only changes the anatomical structure of the foot but also modifies the gait pattern [9,23]. We need to bear in mind that the toes are a crucial element in increasing the weight-bearing area during walking [6], as well as the first metatarsophalangeal joint complex, an important component in both stance and propulsive phases of gait [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we need to adapt our locomotor pattern to compensate for the dysfunction. The research revealed that even a partial loss of the toes not only changes the anatomical structure of the foot but also modifies the gait pattern [9,23]. We need to bear in mind that the toes are a crucial element in increasing the weight-bearing area during walking [6], as well as the first metatarsophalangeal joint complex, an important component in both stance and propulsive phases of gait [16].…”
Section: Introductionmentioning
confidence: 99%
“…Human foot bones form three strong arches: two lengthwise and one across the foot. Arch structures and toes are recognised as critical to gait because of the large range of motion displayed by the ankle [23].…”
Section: Introductionmentioning
confidence: 99%
“…Wright et al [4] reported that foot arch deformations and body sway were significantly correlated during quiet standing, indicating that the arch was related to postural sway. Kelly et al [5] have reported that there is a correlation in the change of CoP and the activity of the plantar intrinsic foot muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Because most of the previous studies used a large scale device to investigate the role of the foot arch on postural control, subject selection was limited. Wright et al [4] used a linear transducer and force plate to examine the relationship between the deformation of the foot arch and CoP sway in seven subjects. Kelly et al [5] measured body sway and muscle activity of the plantar intrinsic muscles in ten young people, using a wire electrode electromyogram and force plate.…”
Section: Effects On Posture Control By Foot Arch Structurementioning
confidence: 99%
See 1 more Smart Citation